Coincidences of self-maps on Klein bottle fiber bundles over the circle - Silva, Weslem L.; Vieira, João Peres [UNESP] (My University, 2012)
The main purpose of this work is to study coincidences of fiber-preserving self-maps over the circle S 1 for spaces which are fiberbundles over S 1 and the fiber is the Klein bottle K. We classify pairs of self-maps over S 1 which can be deformed fiberwise to a coincidence free pair of maps. © 2012 Pushpa Publishing House.
Keywords: Abelianized obstruction; Coincidence; Fiber bundle; Fiberwise homotopy